Do Patients Live Longer After THA and Is the Relative Survival Diagnosis-specific?. Issue 6 (June 2018) - Cnudde, Peter; Rolfson, Ola; Timperley, A. John; Garland, Anne; Kärrholm, Johan; Garellick, Göran; Nemes, Szilard
Abstract: Background: Hip replacements are successful in restoring mobility, reducing pain, and improving quality of life. However, the association between THA and the potential for increased life expectancy (as expressed by mortality rate) is less clear, and any such association could well be influenced by diagnosis and patient-related, socioeconomic, and surgical factors, which have not been well studied. Questions/purposes: (1) After controlling for birth year and sex, are Swedish patients who underwent THA likely to survive longer than individuals in the general population? (2) After controlling for relevant patient-related, socioeconomic/demographic factors and surgical factors, does relative survival differ across the various diagnoses for which THAs were performed in Sweden? Methods: Data from the Swedish Hip Arthroplasty Register, linked to administrative health databases, were used for this study. We identified 131, 808 patients who underwent THA between January 1, 1999, and December 31, 2012. Of these, 21, 755 had died by the end of followup. Patient- and surgery-specific data in combination with socioeconomic data were available for analysis. We compared patient survival (relative survival) with age- and sex-matched survival data in the entire Swedish population according to Statistics Sweden. We used multivariable modeling proceeded with a Cox proportional hazards model in transformed time. Results: Patients undergoing elective THA had a slightly improved survival rate compared with the general population for approximately 10 years after surgery. At 1 year after surgery, the survival in patients undergoing THA was 1% better than the expected survival (r = 1.01; 95% confidence interval [CI], 1.01-1.02; p < 0.001); at 5 years, this increased to 3% (r = 1.03; 95% CI, 1.03-1.03; p < 0.001); at 10 years, the difference was 2% (r = 1.02; 95% CI, 1.02-1.03; p < 0.001); and by 12 years, there was no difference between patients undergoing THA and the general population (r = 1.01; 95% CI, 0.99-1.02; p = 0.13). Using the diagnosis of primary osteoarthritis as a reference, hip arthroplasties performed for sequelae of childhood hip diseases had a similar survival rate (hazard ratio [HR], 1.02; 95% CI, 0.88-1.18; p = 0.77). Patients undergoing surgery for osteonecrosis of the femoral head (HR, 1.69; 95% CI, 1.60-1.79; p < 0.001), inflammatory arthritis (HR, 1.49; 95% CI, 1.38-1.61; p < 0.001), and secondary osteoarthritis (HR, 2.46; 95% CI, 2.03-2.99; p < 0.001) all had poorer relative survival. Comorbidities and the Elixhauser comorbidity index had a negative association with relative survival. Level of achieved education (middle level of education: HR, 0.90, 95% CI, 0.87-0.93, p < 0.001; high level: 0.76, 95% CI, 0.73-0.80, p < 0.001) and marital status (single status: HR, 1.33; 95% CI, 1.28-1.38; p < 0.001) were also negatively associated with survival. Conclusions: Whereas it has been known that in most patients, THA improves quality of life, this study demonstrates that it also is associated with a slightly increased life expectancy that lasts for approximately 10 years after surgery, especially among patients whose diagnosis was primary osteoarthritis. This adds further proof of a health-economic value for this surgical intervention. The reasons for the increase in relative survival are unknown but are probably multifactorial. Level of Evidence: Level III, therapeutic study.